2021
DOI: 10.3389/fped.2021.645074
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Healthy Lifestyles Among Adolescents: An Analysis of More Than Half a Million Participants From 32 Countries Between 2006 and 2014

Abstract: The purpose of this study was to provide data regarding the prevalence and trends of adolescents' healthy lifestyles from 32 countries between 2006 and 2014 by sex and age interval. The data used in the present study were derived from the Health Behavior in School-aged Children (HBSC) 2006, 2010, and 2014 international database. Healthy lifestyle was assessed using the combination of daily physical activity, daily fruit and vegetable consumption, <2 h daily on screen-based behaviors, abstinence from alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
4
20
2
Order By: Relevance
“…As in previous research [ 2 , 3 , 12 , 13 ], most adolescents in this study did not meet the recommendations for vegetable (76.0%) and fruit (63.5%) consumption. Establishing healthy dietary habits would, therefore, seem to be another priority from a public health perspective.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…As in previous research [ 2 , 3 , 12 , 13 ], most adolescents in this study did not meet the recommendations for vegetable (76.0%) and fruit (63.5%) consumption. Establishing healthy dietary habits would, therefore, seem to be another priority from a public health perspective.…”
Section: Discussionsupporting
confidence: 52%
“…In the current study, it was also found that most adolescents spent 2 hours or less in SB during their leisure time. Despite this being in line with the SB data stemming from GSHS studies [ 10 , 43 ] that have used the same or similar samples and methods for measuring SB, this finding contradicts the evidence that SB is highly prevalent among adolescents [ 3 , 9 , 60 ], even after school [ 8 ]. Contrary to several studies, where higher participation in PE has been found to be associated with lower SB [ 34 , 36 , 37 ], our study revealed that adolescents with higher participation in PE classes were more likely not to meet SB recommendations.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations